Nasal cancer in England and Wales: an occupational survey. Issue 3 (August 1981) - Acheson, E D; Cowdell, R H; Rang, E H
Abstract : A national survey of the incidence of nasal cancer in England and Wales during the period 1963-7 with special reference to occupation confirmed the well-known increases in incidence of nasal cancer in cabinet makers and wood machinists, together with the absence of any significant increase in carpenters and joiners, and the increases in boot and shoe operatives and repairers, and in nickel smelters in South Wales. The significant excesses of cases found among coalminers, furnacemen in the gas, coke, and chemical industry, and furnacemen and labourers in foundries may be associated with exposure to coal and coke dust or may be spurious. No excess of nasal cancer was found among male textile workers. Excesses of uncertain significance were found among tailors and dressmakers, bakers and pastry cooks, and printers. Apart from the well-known relationships between adenocarcinoma and work in the furniture and footwear industries there is no definite indication in this survey of any association between a particular histological type of nasal tumour and occupation in England and Wales.